Effect of Dietary Supplementation of Aloe Vera and Amla Fruit Powder on the Growth Performance of Broiler Chicken (Indian Journal of Animal Production and Management, 2024)
The study was conducted to observe the  effect of Aloe vera (Aloe barbadensis) and Amla  fruit (Emblica officinalis) powder supplementation  alone and in combination on growth performance of  broiler chicken. Un-sexed, apparently healthy, day old broiler chicks (240 in number) were randomly  allocated to four groups with four replicates having  15 birds in each. Broilers were fed ration as per BIS  (2007) standards. The supplementation of Aloe  vera and Amla fruit powder alone and in  combination showed highly significant (P
Keywords: Aloe vera; Amla fruit powder; growth performance; broiler